The roles of celebrity endorsers' and consumers' vegan identity in marketing communication about veganism - Phua, Joe; Jin, S. Venus; Kim, Jihoon (Jay) (Journal of marketing communications, 2020)
Celebrities endorsing veganism may exert social influence on consumers' attitude toward veganism and behavioral intention to become vegan. A between-subjects online experiment (N = 303) examined the effects of consumers' eating habits (meat eater versus non-meat eater) and celebrities' vegan identity (altruistic motivation versus egoistic motivation) on various outcomes of health communication about veganism. Results of statistical analyses revealed a significant multivariate main effect of consumers' eating habits on health consciousness, intention to spread electronic word-of-mouth (eWOM) about veganism, and behavioral intention to become vegan. The results also reveal interaction effects between vegan celebrity endorsers' motivation and consumers' eating habits on health consciousness, intention to spread eWoM about veganism, and behavioral intention to become vegan. Additionally, moderating effects of source credibility, subjective norms, and identification with the vegan celebrity endorser were found. This study sheds some light on celebrity endorsements of veganism and effects of message framing on consumers' veganism-related attitude and behavioral intention.